The evolution of ephemeral flora in Xinjiang, China: insights from plastid phylogenomic analyses of Brassicaceae - Tian-Wen Xiao; Feng Song; Duc Quy Vu; Ying Feng; Xue-Jun Ge (BMC Plant Biology, 2024)
Abstract Background The ephemeral flora of northern Xinjiang, China, plays an important role in the desert ecosystems. However, the evolutionary history of this flora remains unclear. To gain new insights into its origin and evolutionary dynamics, we comprehensively sampled ephemeral plants of Brassicaceae, one of the essential plant groups of the ephemeral flora. Results We reconstructed a phylogenetic tree using plastid genomes and estimated their divergence times. Our results indicate that ephemeral species began to colonize the arid areas in north Xinjiang during the Early Miocene and there was a greater dispersal of ephemeral species from the surrounding areas into the ephemeral community of north Xinjiang during the Middle and Late Miocene, in contrast to the Early Miocene or Pliocene periods. Conclusions Our findings, together with previous studies, suggest that the ephemeral flora originated in the Early Miocene, and species assembly became rapid from the Middle Miocene onwards, possibly attributable to global climate changes and regional geological events.